Реши уравнение (6x−11)2−2(6x−11)+1=0

(получившуюся дробь не сокращай, записывай в возрастающем порядке).

ответ: x= дробь

PetryxaMakvin PetryxaMakvin    2   23.04.2020 21:46    1

Ответы
IceOneBro IceOneBro  23.04.2020 22:30

(6х-11)2-2(6х-11)+1=0

12х-22-(-12х+22)+1=0

12х-22+12х-22+1=0

24х-43=0

24х=43

х=43/24

ответ: 43/24

ПОКАЗАТЬ ОТВЕТЫ
pollyholly123 pollyholly123  23.04.2020 22:30

Х∈∅

Пошаговое объяснение:

(6x−11)2−2(6x−11)+1=0

12х-22-12х+22+1=0

1=0

Х∈∅

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика